Innovative development of circular systems while ensuring economic security in the industry - Aleksandra Kuzior; Olena Arefieva; Olha Vovk; Paulina Brożek (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This article is devoted to the formation of methodological foundations of the circular economy on the safety of industrial enterprises. The dependence of the system of economic security from the circular economy concept is implemented by the 3 R model. The model is based on the consistency of quantitative, value and normative indicators. These indicators together allow a comprehensive analysis of the dynamics and direction of the process of implementation of technologies of circular use of resources. The main factors of influence of the circular economy concept on the security of industrial enterprises are resource provision, secondary use of materials and results. To establish the sequence of analysis, we used the mathematical toolkit of factor analysis based on determining the set of factors and their forming indicators. The conducted assessment of the impact of the circular economy concept on the system of economic security of industrial enterprises allows us to state the monopoly of individual sectors of industry, and shows the overall picture of dependence without a position on the level of technology renewal and eco-innovation of production support technologies.
Keywords: 650; model; circular economy; economic security; efficiency evaluation; energy efficiency; industrial enterprises; innovative development